2016
DOI: 10.1590/1983-40632016v4638499
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation time of droplets containing thiamethoxam and adjuvants sprayed on sugarcane leaves

Abstract: The spread and evaporation time of droplets deposited on the target affect the application efficiency of pesticides. This study aimed at evaluating the evaporation time of droplets with different sizes, under different levels of relative air humidity, containing thiamethoxam and adjuvants sprayed on sugarcane leaves. Data were collected in a climate chamber with controlled conditions, where a digital microscope was set up to record the droplet images. The evaporation time was evaluated considering three relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The test results highlighted the importance of sprayer automation based on the psychrometric air conditions at application time. Coarse droplets are susceptible to psychrometric air conditions (Maciel et al, 2018) -although in smaller proportions -in comparison to fine droplets, fact that corroborates the study by Cunha et al (2016).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The test results highlighted the importance of sprayer automation based on the psychrometric air conditions at application time. Coarse droplets are susceptible to psychrometric air conditions (Maciel et al, 2018) -although in smaller proportions -in comparison to fine droplets, fact that corroborates the study by Cunha et al (2016).…”
Section: Resultssupporting
confidence: 86%
“…According to Maciel et al (2017a), up to 27% of the applied liquid volume may be lost depending on the operational condition. Yu et al (2009), Xu et al (2010) and Cunha et al (2016), observed that the lower the relative air humidity, the higher the droplet evaporation rate, i.e., the evaporation time is associated with droplet diameter. In other words, the largest droplets require more time to evaporate.…”
Section: Introductionmentioning
confidence: 99%
“…It is a similar case in Argentina, where there is a presence of thiamethoxam in the C horizon soil (mineral layers that have been affected by pedogenetic processes in a minimal way) with high leaching capacity to groundwater [14]. In addition, the presence of thiamethoxam in water and soil ( Figure 6) reinforce the theory of chemical contaminants migration, where the highest concentrations of pesticides are present at lower depths of soil, mainly in shallow waters [3,21]. On the other hand in soils of loamy sandy texture, with guava plantations in Venezuela, good aeration, medium permeability and little retention of water and nutrients was observed, which allowed for thiamethoxam absorption isotherms with values of 2.95 ± 0.83 mg/kg.…”
Section: Discussionmentioning
confidence: 64%
“…), 24 crabapple ( Malus sylvestris (L.) Mill. ), 25 and sugarcane ( Saccharum officinarum L.), 26 (ii) leaf surface micromorphology as evaluated on the leaves of spindle pelargon ( Pelargonium stenopetalum Ehrh.) and peppermint‐scented pelargon ( P. tomentosum Jacq.…”
Section: Introductionmentioning
confidence: 99%